Analysis of the genetic evolution and recombination of the PRRSV-2 GP2 protein in China from 1996 to 2023 - Kexin Liu; Chen Lv; Cuihua He; Jiankun Pang; Chunyao Lai; Siliang Chen; Ruining Wang; Weili Kong; Jun Ma; Mengmeng Zhao (Microbiology Spectrum)
ABSTRACT Porcine reproductive and respiratory syndrome (PRRS) is among the most serious infectious diseases of pigs worldwide. It is caused by PRRSV and frequently mutates and recombines. To date, however, there have been relatively few studies that have analyzed the GP2 membrane protein of this virus. In this study, we compared 570 nucleotide sequences of the PRRSV-2 GP2 protein obtained from the NCBI GenBank database, which were subjected to phylogenetic analysis. We selected 64 representative strains to investigate the genetic evolution and recombination of the GP2 protein in China. Lineages 1 and 8 were the most prevalent, while lineages 5 and 8 showed closer genetic relationships. The nucleotide similarities of the 570 GP2 sequences ranged from 83.0% to 100%, with amino acid similarities from 80.2% to 100%. Recombinant analysis indicated lineage 1 strains had the highest recombination probability. Comparison of amino acid sequences showed substitutions without deletions or insertions, with lineage 1 exhibiting the most substitutions and lineage 8 the fewest. These findings enhance understanding of PRRSV-2 genetic variation and provide a foundation for further studies on GP2 and vaccine development.IMPORTANCEPorcine reproductive and respiratory syndrome virus (PRRSV) has caused significant losses and posed threats to the swine breeding industry. To date, there have been comparatively few studies on the GP2 protein of PRRSV-2, and consequently, many unanswered questions remain regarding its pathogenicity-associated mechanisms and effects. We collected 570 nucleotide sequences of the GP2 protein of this virus and used these data to perform multifaceted analytical work in order to facilitate the understanding of the genetic evolution of this virus and recombinant mutations. These provide basic data for the follow-up study of GP2 and lay a foundation for further in-depth studies of this virus and vaccine development.